Alpha-synuclein oligomers and small nerve fiber pathology in skin are potential biomarkers of Parkinson’s disease - Vacchi, Elena; Senese, Camilla; Chiaro, Giacomo; Disanto, Giulio; Pinton, Sandra; Morandi, Sara; Bertaina, Ilaria; Bianco, Giovanni; Staedler, Claudio; Galati, Salvatore; Gobbi, Claudio; Kaelin-Lang, Alain; et al. (NPJ Parkinson's Disease, 2021)
The proximity ligation assay (PLA) is a specific and sensitive technique for the detection of αSyn oligomers (αSyn-PLA), early and toxic species implicated in the pathogenesis of PD. We aimed to evaluate by skin biopsy the diagnostic and prognostic capacity of αSyn-PLA and small nerve fiber reduction in PD in a longitudinal study. αSyn-PLA was performed in the ankle and cervical skin biopsies of PD ( n = 30), atypical parkinsonisms (AP, n = 23) including multiple system atrophy (MSA, n = 12) and tauopathies (AP-Tau, n = 11), and healthy controls (HC, n = 22). Skin biopsy was also analyzed for phosphorylated αSyn (P-αSyn) and 5G4 (αSyn-5G4), a conformation-specific antibody to aggregated αSyn. Intraepidermal nerve fiber density (IENFD) was assessed as a measure of small fiber neuropathy. αSyn-PLA signal was more expressed in PD and MSA compared to controls and AP-Tau. αSyn-PLA showed the highest diagnostic accuracy (PD vs. HC sensitivity 80%, specificity 77%; PD vs. AP-Tau sensitivity 80%, specificity 82%), however, P-αSyn and 5G4, possible markers of later phases, performed better when considering the ankle site alone. A small fiber neuropathy was detected in PD and MSA. A progression of denervation not of pathological αSyn was detected at follow-up and a lower IENFD at baseline was associated with a greater cognitive and motor decline in PD. A skin biopsy-derived compound marker, resulting from a linear discrimination analysis model of αSyn-PLA, P-αSyn, αSyn-5G4, and IENFD, stratified patients with accuracy (77.8%), including the discrimination between PD and MSA (84.6%). In conclusion, the choice of pathological αSyn marker and anatomical site influences the diagnostic performance of skin biopsy and can help in understanding the temporal dynamics of αSyn spreading in the peripheral nervous system during the disease. Skin denervation, not pathological αSyn is a potential progression marker for PD.